THE IMPACT OF ADOLESCENT UNINTENDED PREGNANCY ON PREGNANCY CARE: LITERATURE STUDY - Ermiati Ermiati; Nidya Fildza Hadiani; Yulpiana Arunita; Atin Janatin (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Pregnancy in adolescents causes psychological impacts such as shame, fear, depression and even the desire to commit suicide. This condition has an impact on the treatment of pregnancy. The aim of this review literature is to determine unwanted pregnancy versus pregnancy in adolescents. The used method is narrative review using a systematic review of Preferred Reporting Items for Sytematic Review (PRISMA). The data base that used in this literature is Google Scholar and Pubmed. Literature search based on qualitative study design criteria, national and international articles, year published the last 10 years (2010-2020) in Indonesian and English by using Indonesian keywords namely unwanted pregnancy, adolescents, school children and pregnancy care. While English keywords are Adolescent Pregnancy OR Adolescence pregnancies OR Adolescenct pregnancy OR Adolescenct pregnancies OR Teen pregnancy OR Teen pregnancies OR Unwanted Pregnancy OR Unwanted Pregnancies OR Unintended Pregnant OR Unintented Pregnancy OR Unplanned Pregnancy OR Pregnancy Care OR Pregnancies Care OR Antenatal Care. Research articles rated critical appraisal cheklis from JBI. From the 6 articles reviewed, it was found that there were 10 impacts of unwanted pregnancy (KTD) on pregnancy care in adolescemts, including: adolescents are not doing Antenatal Care (ANC) during pregnancy, teenagers tend to make efforts to abort the womb, do not consume healthy foods with balance nutrition, do not consume blood-increasing tablets, do not do physical activity and exercise, sleep rest is lacking, adolescents tend to ignore personal hygiene, teenagers do not stimulate in the fetus, defensive and depression. Further research can be carried out regarding the needs of adolescents with unwanted physical and psychological support and care during pregnancy.